Malpositioned inferior vena cava filter via dual access endovascular technique - Spencer Lucas, BS; Angela VandenHull, BA; Greg Schultz, MD; Patrick Kelly, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
The use of inferior vena cava filters remains a valuable solution for patients with venous thromboembolism who have contraindications to anticoagulation therapy. Some of the most common complications associated with these devices include malposition or migration. In the present case report, we have described the case of a patient who had presented with an unretrievable, malpositioned filter with struts perforating her duodenum, aorta, and vertebral body. She subsequently underwent a two-surgeon endovascular procedure with complete extrication of the filter struts.